FINANCING STRATEGY TO SUPPORT EXPANSION PROJECT OF AFTERMARKET SERVICES COMPANY (CASE STUDY: GARUDA REPAIR SOLUTIONS) - Nurjanah, Eva
Garuda Repair Solutions is a joint venture company between multinational company (Garuda Global) and a state-owned company (PT Aero Indonesia) that engages in turbine services provision. Operating since 1994, the company plans to expand their business to strengthen its competitive advantages to remain sustain in the heat of competition among power services industry. To expand their capacity for expansion plan the company needs initial investment for 76,615,226,740 rupiah. But, as PT Aero Indonesia is unable to give cash investment and won’t any reduce of the shares proportion, the company must find alternative solutions to fund its investment. This research evaluates investment cost needed for expansion project and select which financing strategy alternatives gives the best return for company and shareholders. The most profitable financing strategy alternatives will use Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), Payback Period (PP), and Return on Investment (ROI) as investment decision parameters besides company’s competitive advantages. US Index analysis will be conducted as financial parameters for assessing repayment capacity of a company. Risk assessment of selected financing strategy will be added to be able discover company’s future risk during the project and prepare to mitigate the risks. This research shows that capital structure with 70% debt and 30% equity gives best result in NPV for 120,212,271,411 rupiah, Profitability Index (PI) for 2.48, Internal Rate of Return (IRR) for 29.30% result above its capital cost 10.33%, Payback Period (PP) for 6.32 years, Return on Investment (ROI) for 29.30% in 2029. In addition, US Index result shows > 1 (1.97) that recommend the use of debt on its financing alternatives for expansion project. Also as a result of debt, the company will obtain tax benefits on its interest payment and secured retained earnings.